THE EFFECTIVENESS OF THE MIND MAPPING METHOD ON THE ABILITY TO WRITE BIOGRAPHICAL TEXTS - Kurnia; Lilis Suryani; Nurrahmayani (Adisam Publisher, 2024)
This research aims to describe the effectiveness of the mind mapping method on the ability to write biographical texts in class X SMA Negeri 5 Soppeng. The population in this study was 249, while the sample selected in this study was34 students divided into 12 men and 22 women using purposive sampling techniques. Due to the limited sample size, the research design used was a pre- test and post-test group design. The instruments used to collect data are test sheets and observations. Then, data collection techniques were carried out using test and non-test techniques. The data analysis techniques applied in this research are non-parametric descriptive and inferential statistics because the prerequisite tests were not met. The results of data analysis in this study showed that the average student score was 74.91 at the pre-test stage and there was an increase at the post-test stage to 80.05. Then, at the pre-test stage the number of students who completed was only 16 students or 52.94% and there was a change at the post-test stage to 91.17% or 31 students who completed. The results of hypothesis testing also show significant differences between the pretest and posttest stages. NThe significance value in this study is (0.000) smaller than the generally chosen significance level (usually 0.05). This means that there is a significant difference in performance or test results between before (pretest) and after (posttest) a particular intervention or event in the sample being analyzed. Based on this, it can be concluded that the Mind Mapping method is effectively applied in learning Indonesian, especially the subject of biographical texts.